2008
DOI: 10.1097/brs.0b013e3181644641
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Practice Implications of the Bone and Joint Decade 2000–2010 Task Force on Neck Pain and Its Associated Disorders

Abstract: The best available evidence suggests initial assessment for neck pain should focus on triage into 4 grades, and those with common neck pain (Grade I and Grade II) might be offered the listed noninvasive treatments if short-term relief is desired.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
135
0
22

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 203 publications
(162 citation statements)
references
References 24 publications
5
135
0
22
Order By: Relevance
“…Previous studies reported that between 34−51% of office workers experienced low back pain in the preceding 12 months 1,3) and that 20−23% of office workers reported new onset of low back pain during 1-year follow-up 11,12) . Neck and low back pain occur episodically over a lifetime with variable recovery between episodes 13) . In a working population, between 60−80% of workers with neck pain reported neck pain 1 year later 14) , whereas between 24−61% of patients with recent onset of low back pain developed chronicity 15,16) .…”
mentioning
confidence: 99%
“…Previous studies reported that between 34−51% of office workers experienced low back pain in the preceding 12 months 1,3) and that 20−23% of office workers reported new onset of low back pain during 1-year follow-up 11,12) . Neck and low back pain occur episodically over a lifetime with variable recovery between episodes 13) . In a working population, between 60−80% of workers with neck pain reported neck pain 1 year later 14) , whereas between 24−61% of patients with recent onset of low back pain developed chronicity 15,16) .…”
mentioning
confidence: 99%
“…21,22 It is, however, worthwhile to note that a strengthening component was used in fewer than half of all patients treated in this study. Passive treatments, such as soft-tissue massage, still tended to be popular despite warnings of clinical dependence and ineffectiveness for WAD sufferers.…”
Section: Discussionmentioning
confidence: 99%
“…19,23 Another compounding factor in the choice of management is the patient's preference for health care and choice of care, which is influenced by personal and environmental experiences. 22 The jury is still out on the effect that patient preferences have on clinical outcomes, 24 but it does need to be taken into consideration.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to LBP, neck pain is also one of the most commonly reported symptoms seen in primary care offices [8,9]. According to a study published in 2015 by Cohen et al, neck pain has an annual prevalence rate exceeding 30% and is the fourth leading cause of disability in the United States [10].…”
Section: Introductionmentioning
confidence: 99%